TINJAUAN TEKNOLOGI PENGOLAHAN LEACHATE DI TEMPAT PEMBUANGAN AKHIR (TPA) SAMPAH PERKOTAAN - Purwanta, Wahyu (Center for Environmental Technology, 2007)
Leachate is defined as a liquid, which flows through waste and extracts suspended material or their suspension. In most landfill, leachate is consist of liquids that go into the landfill, which originated from outside the landfill, such as surface drainage, rain water, ground water, water from spring water and other liquids which produced from waste decomposition. The existence of pollutant material or minerals in water body that is originated from leachate will propose the growth of microorganisms, which are harmful for human health and reduce the aesthetic.Ã‚Â Leachate handling could be done with several methods, such as: utilization of hydrolic characteristics by ground water adjustment, thus the leachate flows would not go into the direction of ground water. Another way of leachate handling are: landfill isolation, in order to prevent the inflow of external water and the outflow of leachate water; site selection of an area, which has a good capability of pollutant neutralization; leachate recirculation to be redirected to the solid waste pile; flowing the leachate to domestic waste treatment system and leachate processing with a certain system.Ã‚Â Some processing techniques that are often to be used are: physical-chemical processing, such as coagulation-flocculation-settling; aerobic processing (activated sludge, stabilization pond or aeration pond); anaerobic processing, such as stabilization pond and utilization of sorption characteristics, such as active carbon. The aerobic stabilization pond system is suitable for Indonesian condition due to the availability of sunlight, simple, relatively cheap and their capability of BOD reduction above of 90% and COD reduction of above 80%.Kata Kunci : Leachate, TPA sampah, teknologi pengolahan.